Stage‐directed individualized therapy in esophageal cancer. Issue 1 (6th July 2016) - Goense, Lucas; van Rossum, Peter S.N.; Kandioler, Daniela; Ruurda, Jelle P.; Goh, Khean‐Lee; Luyer, Misha D.; Krasna, Mark J.; van Hillegersberg, Richard
Abstract : Esophageal cancer is the eighth most common cancer worldwide, and the incidence of esophageal carcinoma is rapidly increasing. With the advent of new staging and treatment techniques, esophageal cancer can now be managed through various strategies. A good understanding of the advances and limitations of new staging techniques and how these can guide in individualizing treatment is important to improve outcomes for esophageal cancer patients. This paper outlines the recent progress in staging and treatment of esophageal cancer, with particularly attention to endoscopic techniques for early‐stage esophageal cancer, multimodality treatment for locally advanced esophageal cancer, assessment of response to neoadjuvant treatment, and the role of cervical lymph node dissection. Furthermore, advances in robot‐assisted surgical techniques and postoperative recovery protocols that may further improve outcomes after esophagectomy are discussed.